PREVENTING DENTAL PLAQUE FORMATION AFTER SCALING: AIRFLOW VERSUS POLISH - Ana-; Cristian Funieru; El Saqqa Khaled-Ahmed; Adrian Teodor Țandără; Silviu-Mirel Pițuru; Oana Slușanschi (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: This study was designed in order to compare the efficiency of preventing dental plaque formation after scaling by two methods: conventional dental polish and airflow. Materials and methods: The study was an experiment developed on 30 extracted teeth which were cut longitudinally in two equal pieces. The teeth were first scaled and then one half of each tooth was polished conventionally and the other half was smoothed using airflow protocol. Optical and electronical microscope analysis were performed for both surfaces. Remaining Calculus Index (RCI) and Roughness Loss of Tooth Substance Index (RLTSI) were calculated, and measurements of roughness using Form Talysurf i-Series PRO device were conducted. Results: The RLTSI scores after conventional dental polish were significantly lower (p < 0.05). Conclusions: Conventional dental polish seems to be more efficient in preventing dental plaque formation.